A Bibliometric Analysis of Sustainability in Future Education: Trends and Future Agenda (Sains Humanika, 2022)
This paper aims to investigate the current trends and future sustainability agenda in future education using bibliometric analysis. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was used to select relevant documents for this bibliometric and content study. A quality assessment has been applied in this review; this review mainly focused on mapping the existing literature on sustainability and future education. The quality assessment started by only considering original research articles, excluding all conferences and proceedings articles. Moreover, the review narrowed the subject areas to social science, arts and humanities, and computer science. Finally, all articles were selected from 2011 to 2020; all research before 2011 was excluded from the search. An analysis was conducted into related publications and a bibliometric mapping, classifying major journals indexed by the Scopus database under its primary collection. With a focus on scientific publications, this paper examines types of publications, the quantity of publications, countries, most cited publications, and the most prolific authors. The current review presents a reference for further research and studies based on five main research areas: sustainability in education, future education; Education for Sustainable Development; sustainable learning process; and Sustainable development Goals. The primary conclusion that this review recommends is the high need for a change in the function and role of higher education institutions to investigate sustainability roles in education due to their prominent role in today’s world.
Keywords: Future sustainability agenda, future education, sustainability education, bibliometric analysis.